Scaling Roll Call Votes with wnominate in R - Keith Poole; Jeffrey B. Lewis; James Lo; Royce Carroll (Journal of Statistical Software, 2011)
This paper presents a software package designed to estimate Poole and Rosenthal W-NOMINATE scores in R. The package uses a logistic regression model to analyze political choice data, usually (though not exclusively) from a legislative setting. In contrast to other scaling methods, W-NOMINATE explicitly assumes probabilistic voting based on a spatial utility function, where the parameters of the utility function and the spatial coordinates of the legislators and the votes can all be estimated on the basis of observed voting behavior. Building on software written by Poole in Fortran, the new wnominate package in R facilitates easier data input and manipulation, generates bootstrapped standard errors, and includes a new suite of graphics functions to display the results. We demonstrate the functionality of this package by conducting a natural experiment using roll calls -- an experiment which is greatly simplified by the data manipulation capabilities of the wnominate package in R.